Taxonomic and ecological studies of the Genus simulium (Diptera: Simuliidae) in Peninsular Malaysia / Zubaidah Ya'cob - Zubaidah, Ya'cob (2016)
A thorough black fly investigation was carried out in Peninsular Malaysia (1) to report the detailed identification keys and taxonomic descriptions of new species, (2) to elucidate their nationwide distribution pattern and (3) to investigate their assemblage pattern along an elevational gradient. Five new species, Simulium vanluni, Simulium ledangense, Simulium pairoti and Simulium azhari and Simulium johorense were discovered and described based on mature larva, pupa, male and female. A total of 47 Simulium species were revealed through the nationwide surveys in Peninsular Malaysia. The most frequently collected species were Simulium trangense, followed by Simulium angulistylum, Simulium cheongi, Simulium tani, Simulium vanluni, Simulium sheilae and Simulium bishopi. Simulium vanluni, Simulium trangense and Simulium angulistylum were the three most abundant species. High species richness was associated with larger, deeper, faster and higher discharge streams with larger streambed particles, more riparian vegetation and low pH. Simulium vanluni and Simulium tani prefer large, fast flowing streams with higher pH, large streambed particles and riparian trees. Simulium bishopi was commonly found at high elevation with cooler stream, low conductivity and more riparian trees. In contrast, Simulium sheilae was positively related with streams at low elevation, warmer stream with low conductivity and less riparian trees. On the other hand, a total of 35 black fly species were recorded along an elevational gradient. The most frequently collected species were Simulium tani and Simulium whartoni, while the relatively common species were Simulium sp. (nr. feuerborni), Simulium decuplum, Simulium angulistylum, Simulium bishopi and Simulium izuae. Six simuliid species were distributed below 500 m, whereas eight species were distributed above 1,400 m. Simulium sp. (nr. feuerborni) and Simulium asakoae were found from middle to high elevations (711–1,813 m). Simulium whartoni, Simulium brevipar and Simulium bishopi were distributed widely from low to high elevations (159–1,813 m). Regression analysis between species richness and PCs revealed that the species richness was significantly associated with wider, deeper and faster streams at low elevation, water temperature 23°C–25°C, low conductivity, higher discharge, more canopy cover and riparian vegetation and with larger streambed particles. Forward logistic regression indicated four species were significantly related to the stream variables (Simulium whartoni, Simulium sp. (nr. feuerborni), Simulium tani and Simulium angulistylum). Canonical correspondence analysis indicated that the temperature, stream size and discharge were the most important factors contributing to the separation of the stream sites from different elevation and hence are the predictors for the distribution of black fly species assemblages. The present study has provided new insights into the black fly species composition and diversity in Peninsular Malaysia and these findings will be the stepping stone promoting more black fly studies in Malaysia as well as other countries in Southeast Asia.